2019
DOI: 10.1063/1.5111944
|View full text |Cite
|
Sign up to set email alerts
|

Roles of silver nanoclusters in surface-enhanced Raman spectroscopy

Abstract: The cause for the huge enhancement factors of surface-enhanced Raman spectroscopy (SERS) by the addition of small silver nanoclusters is theoretically investigated focusing on the difference between resonance Raman activity and surface plasmon effects. First, the resonance and off-resonance Raman spectra are calculated using the incident light wavenumbers of the low-lying charge transfer excitations for the surface (S) and vertex (V) complexes of pyridine molecule attaching to three small silver nanoclusters: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 53 publications
(57 reference statements)
1
12
0
Order By: Relevance
“…Further insights on the adsorption geometry of AZ on silver surface could be theoretically achieved by performing calculations modeling the substrate with as slab or increasing the number of atoms [73][74][75][76][77][78][79][80][81][82][83] and experimentally by using other techniques such as X-ray photoelectron spectroscopy (XPS) and Near Edge X-Ray Absorption Fine Structure (NEXAFS) spectroscopy [38,39,43,84].…”
Section: Discussionmentioning
confidence: 99%
“…Further insights on the adsorption geometry of AZ on silver surface could be theoretically achieved by performing calculations modeling the substrate with as slab or increasing the number of atoms [73][74][75][76][77][78][79][80][81][82][83] and experimentally by using other techniques such as X-ray photoelectron spectroscopy (XPS) and Near Edge X-Ray Absorption Fine Structure (NEXAFS) spectroscopy [38,39,43,84].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon could be explained using two different theories-the electromagnetic and chemical theories. The electromagnetic theory has strong experimental support [27] and will be the only one discussed in this section.…”
Section: Theoretical Background Of Surface Enhanced Raman Spectroscopy Techniquesmentioning
confidence: 99%
“…An optimal scale factor for harmonic frequencies being 1.0353 was applied [53]. The Ag 20 pyramidal cluster which has been recommended by several computational works in literature is used to reproduce the AgNPs surface model [37][38][39][40][41][42][43][44]52]. Geometries of all possible interaction configurations between the THR and Ag 20 clusters are optimized in the gas phase with tight convergence criteria and an ultrafine integration grid and loose symmetry.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Several papers have been published on this topic, including studies on large and complicated molecules like Tinuvin P [32], crystal violet [33], paroxetine [34], amoxicillin [35], and L-valine phosphonate dipeptides [36]. Many authors have utilized pyramidal Ag 20 or Au 20 clusters as models to reproduce the NPs surfaces [37][38][39][40][41][42][43][44], although it has recently been reported that these models are not the most stable cluster isomers [45]. Despite this harsh simplification, these works provide valuable insight into the interaction of different molecules onto SERS substrates.…”
Section: Introductionmentioning
confidence: 99%